Residuos orgánicos en una economía circular (2018)
As a solution to the management of organic waste, technologies such as anaerobic digestion, natural process, are available, by which organic material is degraded by different groups of microorganisms in an airtight, isolated place, with fermentation and in the absence of oxygen, thus reducing the emissions of methane emitted by the disposal, treatment and management of solid waste in sanitary landfills closing cycles of biological material and reducing the linear economy of landfill, to finally produce: Gas with higher percentage in methane, Solid organic fertilizer (compost), Organic fertilizer liquid (digestate).